EFEKTIVITAS MODEL PEMBELAJARAN KONSTRUKTIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Dhea Afif Anandari; Stefanus Christian Relmasira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of constructive learning models in improving mathematical problem-solving abilities in mathematics learning of grade IV students of Kutowinangun 12 Elementary School on multiplication and division materials, and to determine the comparison of the results of students' mathematical problem-solving abilities between classes that apply constructive learning models and classes that apply conventional learning models on multiplication and division materials. This study uses a quasi-experimental research method with a Nonequivalent Control Group Design experimental design. The object of the study was elementary schools within the Muwardi Cluster in Tingkir District, Salatiga City, Central Java. Based on the results of the study, it was found that the results of the t-test collection (average difference test) based on the results of the students' posttest showed that the sig value (2-tailed) was 0.000 <0.05. The average posttest learning outcomes showed different results, namely in the experimental group 87.07, while in the control group it had an average of 72.87. It can be concluded that Ho is rejected, while Ha is accepted. This shows that there is a difference in effectiveness and it can be concluded that the constructive learning model is more effective in improving students' mathematical problem-solving abilities in elementary schools than learning with conventional models.